IMPLEMENTATION OF PRINCIPAL ACADEMIC SUPERVISION IN DISTANCE LEARNING (PJJ) DURING THE COVID 19 PANDEMIC - SULISTIAWATI, Lilis (Journal of Education and Leadership in Education, 2022)
This study aims to describe the optimization of the implementation of distance learning (PJJ) by teachers under the academic supervision of the principal at SDN Karawaci Baru 2, Tangerang City. Distance learning in Tangerang City is suspected to have many obstacles. These problems include a) the implementation of the national curriculum has not been implemented comprehensively, b) the lack of preparation from educators in implementing online learning, c) the affective assessment aspect in online learning is not optimal due to distance limitations. This research is a quantitative descriptive study using the research flow, namely planning, implementation, results and follow-up. The subjects of this study were school principals and teachers at SDN Karawaci Baru 2, Tangerang City. Data collection was carried out in April–May 2022 through observation, interviews and documentation. It was concluded that the implementation of academic supervision of teachers could optimize the implementation of distance learning during the COVID 19 pandemic. Teacher supervision and motivation greatly determine the success of distance learning, both individually and in small groups.